2023
DOI: 10.1038/s41467-022-35583-w
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of SNX9 alleviates CD8 T cell exhaustion for effective cellular cancer immunotherapy

Abstract: Tumor-specific T cells are frequently exhausted by chronic antigenic stimulation. We here report on a human antigen-specific ex vivo model to explore new therapeutic options for T cell immunotherapies. T cells generated with this model resemble tumor-infiltrating exhausted T cells on a phenotypic and transcriptional level. Using a targeted pooled CRISPR-Cas9 screen and individual gene knockout validation experiments, we uncover sorting nexin-9 (SNX9) as a mediator of T cell exhaustion. Upon TCR/CD28 stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 100 publications
2
24
0
Order By: Relevance
“…Spontaneous NFkB activation in SKM-BBz CAR-T cells (Figure 4D and Table 1) may explain NR4A upregulation, as there is a report that NR4A molecules are upregulated in macrophages in response to NFkB signaling. 30 Since SKM-BBz CAR-T cells also express other exhaustion-related genes such as SNX9 31 and DNMT3A 32 at the same level as SKM-28z CAR-T cells (Figure 5C), we speculate that SKM-BBz CAR-T cells may be in an early stage of exhaustion. In the chronic viral infection model, exhausted T cells are divided into four sequential stages; progenitor 1 (Tex prog1 ), progenitor 2 (Tex prog2 ), intermediate (Tex int ), and terminal (Tex term ).…”
Section: Discussionmentioning
confidence: 88%
“…Spontaneous NFkB activation in SKM-BBz CAR-T cells (Figure 4D and Table 1) may explain NR4A upregulation, as there is a report that NR4A molecules are upregulated in macrophages in response to NFkB signaling. 30 Since SKM-BBz CAR-T cells also express other exhaustion-related genes such as SNX9 31 and DNMT3A 32 at the same level as SKM-28z CAR-T cells (Figure 5C), we speculate that SKM-BBz CAR-T cells may be in an early stage of exhaustion. In the chronic viral infection model, exhausted T cells are divided into four sequential stages; progenitor 1 (Tex prog1 ), progenitor 2 (Tex prog2 ), intermediate (Tex int ), and terminal (Tex term ).…”
Section: Discussionmentioning
confidence: 88%
“…Genes that cluster together with such may have an effect on T cell persistence and exhaustion ( Fig 5E ). For example, it was just recently shown that SNX9 deletion alleviates T cell exhaustion 75 . Detailed analysis of TFs that are strongly associated with driving exhaustion ( RUNX1 and PRMD1 ), as well as being a marker for tumor-reactive TILs ( SOX4 ) visualizes their impact on T cell differentiation towards the exhausted state ( Fig 5G ).…”
Section: Resultsmentioning
confidence: 99%
“…While some statistical analysis issues can be addressed by increasing the selective pressure or increasing the number of cells and replicates, these solutions can be challenging or infeasible for in vivo screens. For this reason, it is very common to see high‐profile studies opt to use a simple fold change to determine hits rather than use any of the CRISPR analysis strategies available 17,37,126,127 . Unfortunately, this simple method will fall short when analyzing any screen design more complicated than screen‐vs‐control.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…For this reason, it is very common to see high-profile studies opt to use a simple fold change to determine hits rather than use any of the CRISPR analysis strategies available. 17,37,126,127 Unfortunately, this simple method will fall short when analyzing any screen design more complicated than screen-vs-control. Another major bottleneck with screens in cancer immunology is the high clone dropout of in vivo CRISPR screens.…”
Section: Representative Challenges In Crispr Screening For Future Opt...mentioning
confidence: 99%